2010
DOI: 10.1152/ajpheart.00872.2009
|View full text |Cite
|
Sign up to set email alerts
|

Time course of carotid artery growth and remodeling in response to altered pulsatility

Abstract: Elucidating early time courses of biomechanical responses by arteries to altered mechanical stimuli is paramount to understanding and eventually predicting long-term adaptations. In a previous study, we reported marked long-term (at 35-56 days) consequences of increased pulsatile hemodynamics on arterial structure and mechanics. Motivated by those findings, we focus herein on arterial responses over shorter periods (at 7, 10, and 14 days) following placement of a constrictive band on the aortic arch between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 42 publications
9
52
1
Order By: Relevance
“…Altered hemodynamics, increases in flow and pressure with the intrinsic stretch, have been shown to increase vascular stiffening and cause vascular remodeling in the mature vasculature (12,16,20). The mechanotransduction pathways for the vascular remodeling have been well established in the adult where small increases in flow have been observed to stimulate production of nitric oxide (NO), prostacyclin, nitric oxide synthase, platelet-derived growth factor receptor (PDGR)-A, platelet-derived growth factor (PDGF)-B, fibroblast growth factor (FGF)-1, FGF-2, TGF-␤, interleukin-1 and -6, and intercellular adhesion molecule-1 while downregulating vascular cell adhesion molecule-1 (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered hemodynamics, increases in flow and pressure with the intrinsic stretch, have been shown to increase vascular stiffening and cause vascular remodeling in the mature vasculature (12,16,20). The mechanotransduction pathways for the vascular remodeling have been well established in the adult where small increases in flow have been observed to stimulate production of nitric oxide (NO), prostacyclin, nitric oxide synthase, platelet-derived growth factor receptor (PDGR)-A, platelet-derived growth factor (PDGF)-B, fibroblast growth factor (FGF)-1, FGF-2, TGF-␤, interleukin-1 and -6, and intercellular adhesion molecule-1 while downregulating vascular cell adhesion molecule-1 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic stress in adult arteries has been shown as an important modulator in vascular ECM composition and stiffness (12,20). The fetal cardiovascular system in utero receives growth and development signaling from hemodynamic forces during the fetal and neonatal period (6,7) and is highly susceptible to abnormal vascular constitutive remodeling due to abnormal hemodynamic stress (1).…”
mentioning
confidence: 99%
“…We found that the in vivo axial carotid artery length was smaller in D257A mice (Figure 1G-H). Axial remodeling has been observed in mice with elevated pressures from an aortic banding procedure (Eberth et al, 2010). This length reduction may be a mechanism to compensate for the circumferential remodeling (Humphrey et al, 2009) or simply a result of the higher pressures that cause more circumferential than axial stretch due to known differences in circumferential and axial elastic moduli (Dobrin and Doyle, 1970; Guo and Kassab, 2003; Tanaka and Fung, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism for this relationship is mechanical; arterial stiffening can increase systolic blood pressure via an early return of the reflected pressure waves generated from ventricular ejection (Safar et al, 2003). The resulting increased pressures cause endothelial and smooth muscle cell (SMC) dysfunction and arterial collagen accumulation (Eberth et al, 2010; Lee and Oh, 2010) and subsequently increased ventricular afterload (Kelly et al, 1992), which can eventually lead to heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…The same group also observed that the thickness of the outer lamellar units grew more rapidly than that of the inner units. Eberth et al [10] studied morphological changes in rat carotid arteries for a period of 56 weeks and found an increase in the internal radius from 531 µm to 592 µm, accompanied by an increase in thickness from 23.1 µm to 85.7 µm.…”
Section: Motivationmentioning
confidence: 99%